The relationship of anterior occlusion and skeletal variables with the frontal sinus index: an analytical cross-sectional study - Arif, Tahira; Sadia Rizwan; Imtiaz Ahmed; Waqas Ahmed Farooqui (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the relationship of anterior occlusion and skeletal variables with the frontal sinus index. Method: The retrospective, analytical, cross-sectional, study was conducted from July to November 2020 at Dr Ishrat-ul-Ebad Khan Institute of Oral Health Sciences and Dow Dental College, Dow University of Health Sciences, Karachi, and comprised data from 2015 to 2018 related to pre-treatment lateral cephalograms for determining frontal sinus index and other cephalometric variables. The dental casts were observed for incisor classification. Patients with Class I incisors formed the comparison group, while the rest comprised 5 malocclusion groups. The frontal sinus was traced, and the sinus index was calculated. Data was analysed using STATA 15 and R 3.5.1. Results: Of the 240 subjects, there were 40(16.66%) in each of the 6 groups; 155(64.6%) females and 85(35.4%) males. The mean age of the sample was 21.33±3.52 years (range: 16-29 years). The mean sinus index was higher in all malocclusion groups than the comparison group, but it was significantly higher only in Class II division 2 and anterior open bite groups (p<0.05). The only exception to the trend was Class II division 1 with and without contact in which the value was lower (p>0.05). The anterior cranial base length, sella-nasion mandibular plane angle, and upper incisor palatal plane angle significantly affected the frontal sinus index (p<0.05). Conclusion: The frontal sinus index could be considered an indicator of harmonious anterior occlusion. Key Words: Frontal sinus, Cephalometry, Dental occlusion, Malocclusion.